Efficacy of ozone therapy as a novel potential therapeutic approach in severe granulomatous mastitis - Cabıoğlu, Neslihan; Can Trablus, Didem; Yalçın, Nesli; Emiroğlu, Selman; Dinç, Nagehan; Tükenmez, Mustafa; Müslümanoğlu, Mahmut; İğci, Abdullah; Özkurt, Enver; Özmen, Vahit; Güven, Yusuf İzzettin; Dinççağ, Ahmet Sait (Springer, 2021)
[Abstract Not Available]
Keywords: Severe Granulomatous Mastitis; Therapeutic Approach; Ozone Therapy